NOGHEH GETAH KEHIDUPAN - Ade Setiawan S1 (Saraswati)
The writing discussed an article with title “Nogheh Getah Kehidupan” that tells us the way of rubber worker’s life with all of its problem. The article was inspired by the rubber worker’s living. Rubber as source of living was obtained with spirit and work hard. Even though a lot of obstruction, but all of obstruction couldn’t stop the rubber worker to work with high spirit and work hard.